A Review of Fiscal Policy Responses to COVID-19 - Lacey, Eric; Massad, Joseph; Utz, Robert (World Bank, Washington, DC, 2021)
Countries around the world adopted a wide range of fiscal measures in 2020 to mitigate the health and economic impacts of the COVID-19 pandemic. At the beginning of 2021, the outlook on the evolution of the pandemic remains uncertain. COVID-19 cases are at high levels in many countries, but effective vaccines have been approved and are being rolled out. The occurrence of new variants of the virus that spread more easily and more quickly and that may be associated with an increased risk of death adds to the uncertainty as to how quickly the pandemic can be brought under control.